Сучасні аспекти пошуку прихованих розділів на диску в контексті цифрової криміналістики - Алфьоров, С. П. (ХНУРЕ, 2025)
The study of hidden partitions within digital storage systems represents a pivotal aspect of contemporary digital forensics. This work critically examines the methodologies employed in concealing storage partitions, including Host Protected Area (HPA), Device Configuration Overlay (DCO), and advanced NTFS-based hiding mechanisms. A comparative analysis of forensic techniques used to detect and interpret these covert partitions is conducted, with an emphasis on their implications for cybersecurity and forensic investigations. Furthermore, this study explores emerging trends in anti-forensic techniques and discusses their potential countermeasures.
Keywords: цифрова криміналістика; пошук прихованих розділів